Analysis of gender violence in the university. Qualitative intervention proposal - Loayza-Maturrano, Edward Faustino (2021)
The situation of gender violence that our society shows is also reflected in our institutions, such as the university. Higher university education institutions are not immune to this phenomenon. This problem can occur in the relationship between students (male and female) and the teacher-student relationship. The purpose of this study is to analyze the violence that occurs against women in universities. The research is of a qualitative type and of a phenomenological design, methodologically developed by means of an interview-type instrument validated through a prior triangulation, which was applied to focus groups of students of both genders in three universities. The type of sampling was for convenience and was represented by 107 students. The results show that there is a non-generalized incidence of gender violence by male students and teachers, which is more significant in the indicators: indirect and covert coercion; which is based on the exercise of power by the male student of higher cycles and teachers. The conclusions corroborate the existence of gender violence, the occurrence of which is determined by the exercise of power by male students and teachers.